2009
DOI: 10.1007/s00415-009-5197-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of the frontal assessment battery in evaluating executive dysfunction in patients with Huntington’s disease

Abstract: The frontal assessment battery (FAB) is a bedside cognitive scale designed to measure executive functions. Huntington's disease (HD) is a neurodegenerative disorder characterized by motor, behavioral, and cognitive dysfunction. The aim of this study was to check the validity of the FAB for the evaluation of cognitive impairment in patients with HD. Forty-one patients diagnosed with HD and 53 healthy controls matched by education, sex and age were evaluated with a validated Brazilian version of the UHDRS, the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 34 publications
7
29
0
Order By: Relevance
“…Second, the capability of the FAB to detect executive dysfunctions in various diseases affecting fronto-striatal circuits constitutes a recent issue. Specifically, the FAB has been effectually used to document the presence of executive dysfunctions in various neurological diseases (e.g., amyotrophic lateral sclerosis [27,28]; Huntington’s disease [29]; multiple system atrophy and progressive supranuclear palsy [30]; Parkinson’s disease [31-34]) and psychiatric disorders (e.g., addictive substance abuse [35,36]; depression in Parkinson’s disease [37,38]). The results of the current study add to this rapidly-growing body of knowledge by strengthening the claim that various indices of FAB performance can be considered as valid assessments of lateral prefrontal, notably anterior insular, functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the capability of the FAB to detect executive dysfunctions in various diseases affecting fronto-striatal circuits constitutes a recent issue. Specifically, the FAB has been effectually used to document the presence of executive dysfunctions in various neurological diseases (e.g., amyotrophic lateral sclerosis [27,28]; Huntington’s disease [29]; multiple system atrophy and progressive supranuclear palsy [30]; Parkinson’s disease [31-34]) and psychiatric disorders (e.g., addictive substance abuse [35,36]; depression in Parkinson’s disease [37,38]). The results of the current study add to this rapidly-growing body of knowledge by strengthening the claim that various indices of FAB performance can be considered as valid assessments of lateral prefrontal, notably anterior insular, functioning.…”
Section: Discussionmentioning
confidence: 99%
“…8,12 One study of 20 mild-to-moderate HD patients found significantly lower scores on the MoCA total score and almost all cognitive domains, compared to normal controls. 8 Another study of 41 HD patients found that the total HD sample scored significantly lower than normal controls on the MMSE; however, performance in each stage of the disease was not compared to normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…8 Another study of 41 HD patients found that the total HD sample scored significantly lower than normal controls on the MMSE; however, performance in each stage of the disease was not compared to normal controls. 12 …”
Section: Discussionmentioning
confidence: 99%
“…8 Forty of the 574 identified cohort studies met the inclusion criteria (Table II). We were able to include 19 studies in the statistical analysis [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. They involved a total of 1939 (44.3% women, n = 14 studies) patients with a mean age of 48.9 AE 2.3 years (n = 13) and a mean baseline TFC score of 10.1 AE 0.7 (n = 11).…”
Section: R E S U L T Smentioning
confidence: 99%